(untitled) (REVUE ROUMAINE DES SCIENCES TECHNIQUES — SÉRIE ÉLECTROTECHNIQUE ET ÉNERGÉTIQUE, 2022)
Photovoltaic (PV) self-consumption is becoming an important aspect of storing and deferring energy generated from distributed solar energy systems. This paper investigates a novel high-gain DC-DC converter for extraction of maximum power from the solar PV system by employing both Incremental Conductance (I&C) and Improved Incremental Conductance (IIC) based on Maximum Power Point Tracking (MPPT) techniques under partial shadow conditions. This proposed converter achieves high step-up voltage gain using voltage doublers and improves the efficiency of the system with low voltage stress on the switch, reduced reverse recovery of diodes, and less duty cycle operation. It avoids the converter operation at extreme duty cycles. The simulation responses to the work have been simulated using a Matlab-Simulink environment and the obtained results are validated through an experimental prototype.